Effects of Sjogren's syndrome and high sugar diet on oral microbiome in patients with rampant caries: a clinical study - Yifei Tang; Hua Nie; Yu Zhang; Yuan Wei; Yequan Huang; Yuan Zhuang; Weidong Yang; Yanan Zhu (BMC, 2024)
Abstract Objective The purpose of this study was to assess the composition of the oral microbial flora of adults with rampant caries in China to provide guidance for treatment. Patients and methods Sixty human salivary and supragingival plaque samples were collected. They were characterized into four groups: patients with rampant caries with Sjogren's syndrome (RC-SS) or high-sugar diet (RC-HD), common dental caries (DC), and healthy individuals (HP). The 16S rRNA V3-V4 region of the bacterial DNA was detected by Illumina sequencing. PCoA based on OTU with Bray-Curtis algorithm, the abundance of each level, LEfSe analysis, network analysis, and PICRUSt analysis were carried out between the four groups and two sample types. Clinical and demographic data were compared using analysis of variance (ANOVA) or the nonparametric Kruskal-Wallis rank-sum test, depending on the normality of the data, using GraphPad Prism 8 (P < 0.05). Results OTU principal component analysis revealed a significant difference between healthy individuals and those with RC-SS. In the saliva of patients with rampant caries, the relative abundance of Firmicutes increased significantly at the phylum level. Further, Streptocpccus, Veillonella, Prevotella, and Dialister increased, while Neisseria and Haemophilus decreased at the genus level. Veillonella increased in the plaque samples of patients with rampant caries. Conclusion Both salivary and dental plaque composition were significantly different between healthy individuals and patients with rampant caries. This study provides a microbiological basis for exploring the etiology of rampant caries. Clinical relevance This study provides basic information on the flora of the oral cavity in adults with rampant caries in China. These findings could serve as a reference for the treatment of this disease.